Recent Advancements in Fish-on-Chip: A Comprehensive Review - Tushar Nath; Hua Tan (Fluids)
Zebrafish (Danio rerio) emerged as a suitable vertebrate model organism in the 1960s, owing to its transparent embryos and ease of breeding. Research utilizing zebrafish as a model organism gained significant momentum in the 1970s, particularly in the field of developmental biology. Over the years, zebrafish has become an indispensable model across various domains of biological research. However, conventional techniques for handling zebrafish in research settings have been limited by challenges related to survival rates, throughput, and imaging capabilities. The advancements in microfluidics and Micro-Electro-Mechanical Systems (MEMS) technology have addressed many of these challenges, enabling significant progress in zebrafish-based studies. The integration of microchannels, which ensure laminar flow for precise liquid handling, alongside microsensors and actuators for trapping mechanisms and high-resolution imaging, has greatly enhanced experimental efficiency and precision. This review provides a comprehensive analysis of very recent advancements in Fish-on-Chip (FOC) technologies, with a focus on their applications in zebrafish research, including trapping, imaging, transportation, and studies involving drug screening and disease modeling. Furthermore, we discuss recent efforts in retaining progressively motile zebrafish sperm, which is increasingly critical to meeting the rising demand for diverse zebrafish lines. Finally, we discuss an automated microfluidic-based fish farm developed using these technologies and conclude the review by highlighting potential future directions for Fish-on-Chip (FOC) technology.